Semi LocallS-LifitingMod.s - et. al., Nada K. Abdullah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To consider is a commutative ring with unity, be a nonzero unitary left -mod., is known semi lifitingmod. if for every subm. N from , ∃subm. A from N so that while is semi small subm.from B.Semi Locall s-lifitingmod. is a strong form from semi lifitingmod., where an -mod. is known semi locall s-lifitingmod. if has aunique semi max.subm. N whileallsubm. B from , ∃subm. A from N so that while N ∩ B is semi small subm.from B.The current study deals with this class frommod.while give several fundamental properties related with this concept.